Advancing scholarly publishing through open access biomedical repositories: A knowledge management perspective. (October 2019) - Kruesi, Lisa; Tanner, Kerry; Burstein, Frada
Scholarly publishing has undergone major changes over the past 50 years. Funder mandates and organisational reporting obligations have heralded the creation of open access repositories, such as institutional and subject repositories. This research draws upon the US PubMed Central (PMC) and Europe PMC, also known as PMC International, as a role model to inform the concept and opportunity for an Australasia open access biomedical repository. PMC International is a leader in making citations and research output, which link to research data, Findable, Accessible, Interoperable and Reusable (FAIR). As repositories approach two decades of development, this paper reports on the potential for an Australasia open access biomedical repository through a knowledge management lens and explores the opportunities for future open access biomedical repositories.